The complexity of Partial edentulism among patients visiting saveetha dental college based on PDI classification (Journal of Pharmaceutical Negative Results, 2022)
Background: Complexity is the state of being irritated or complicated. It varies for each individual. The loss of tooth happens in different manners, the most common being extraction due to non-restorable caries. This loss of tooth affects many attributes of the individual. The functions like speech, chewing are affected. But most importantly it affects the aesthetics of the individual which affects their personality of the person which makes the individual more complex. Aim: The study aims at analyzing the complexity of partial edentulism patients based on PDI classification. Materials and methods: The study involved analyzing a patient with partial edentulism who is visiting Saveetha Dental College. The patients were classified based on age and based on PDI classification. The clinical analysis done was noted in DIASDental Information Archiving Software of Saveetha Dental College. All the data from DiAS was then collected. All collected data were computed in excel format and statistical analysis was done. Results: In this study, a total of 630 patients were examined. Class 1 PDI was more common in both genders. The males had more missing compared to females. Class 1 was found in 36.8% followed by class 3 was 25.1%, then class 2 was 22.5% and the least common was class 4 16%. Conclusion: Within the limitation of the study, it was found that the patients were more complex age group of 40-49 years of age and more willing for treatment in the age group of 29-30 years of age.